(untitled) - Deitel, Harvey M. (Upper Saddle River, NJ, 1999)
Completely revised and updated to cover the new features in the 1.2 release of Java, this book is a comprehensive look at learning how to program in Java. The book covers all facets of the Java language, including object-orientation, multithreading, exception-handling, the new event model, the graphics capabilities of the new Abstract Windows Toolkit, and the new APIs.
Keywords: Java (Computer program language),Java (Chương trình ngôn ngữ máy tính)